Potential gradient distribution type high-temperature anticorrosive coating and preparation method thereof

By adopting a potential gradient distribution design in the high-temperature anti-corrosion coating, and superimposing high-potential, medium-potential and low-potential coatings in sequence, the existing coatings are solved inadequate protection in high-temperature and corrosion environments, and a higher service life and protection efficiency are achieved.

CN119614070APending Publication Date: 2025-03-14AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411681712.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing high-temperature anti-corrosion coatings are difficult to achieve long-life protection in high-temperature and corrosion environments, mainly due to the single potential distribution of the overall coating, which leads to the overall corrosion failure of the coating.

Method used

The potential gradient distribution high-temperature anti-corrosion coating is used, and the coating service life of the coating is extended by superimposing high potential, medium potential and low potential coatings in sequence, and the superposition and adaptation of different potential layers is used.

Benefits of technology

It achieves higher service life and higher protection efficiency in low thickness state, extends maintenance and maintenance cycle, and has excellent protection performance with resistance to 600℃ and neutral salt spray corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614070A_ABST
    Figure CN119614070A_ABST
Patent Text Reader

Abstract

The invention discloses a potential gradient distribution type high-temperature anticorrosive coating and a preparation method thereof, and relates to the technical field of coating materials. The invention relates to a potential gradient distribution type high-temperature anti-corrosion coating which is formed by superposing and combining a high-potential coating, a medium-potential coating and a low-potential coating. The invention provides a potential gradient distribution type high-temperature anticorrosive coating and a preparation method thereof, so that the problems that the potential distribution of the high-temperature anticorrosive coating is single and the overall corrosion failure of the coating is easy to occur are solved, the service life of the coating is longer under the condition that the thickness of the coating is effectively reduced, and the maintenance period is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating materials, and in particular relates to a potential gradient distribution type high temperature anti-corrosion coating and a preparation method thereof. Background Art

[0002] High-temperature boilers, pipelines, engine parts, etc. need to withstand temperatures of 600°C or even higher for a long time. At the same time, in high-temperature gaps, they may also be in an environment of high humidity and high salinity, facing the dual damage of high temperature and corrosion. The comprehensive performance of high-temperature anti-corrosion coatings plays a vital role in the operating life of the entire equipment. Cathodic protection is a relatively effective protection principle for high-temperature anti-corrosion coatings. Metals with a potential lower than that of the substrate steel material are used as high filling phases. Spray coatings are formed through high-temperature relatively stable resin binders to form a dense low-potential protective layer on the surface of the substrate. The metal in the coating is preferentially sacrificed by the principle of galvanic corrosion, thereby delaying the corrosion of the substrate. However, due to the poor toughness of high-temperature adhesive materials, it is usually impossible to apply a high thickness. Generally, the coating can only be used below 100μm. When the cathodic protection reaction occurs, as the filling phase in the coating gradually reacts and consumes, the filling metal cannot form a tight electrical connection, thereby losing the cathodic protection effect on the substrate. The protection life is far from the theoretical protection expectation of the filling metal phase. The reason is that the potential distribution of the overall coating is single, and the overall corrosion failure of the coating is prone to occur. Summary of the invention

[0003] Based on the above background, a potential gradient distribution high temperature anticorrosion coating and its preparation method are proposed. Through the unique and innovative gradient design, the high efficiency and long life anticorrosion effect at low thickness is achieved, and the cathodic protection time sequence of low, medium and high potential coatings is used to extend the service life of the coating.

[0004] In view of this, according to one aspect of an embodiment of the present invention, a potential gradient distribution type high temperature anti-corrosion coating is provided, wherein the coating comprises three coatings, namely, a high potential coating, a medium potential coating and a low potential coating, which are stacked in sequence, wherein the high potential coating is cured by a high potential coating, and the high potential coating also comprises a high potential base material and a curing agent, wherein the high potential base material is a mixture of polymethoxyphenylsiloxane, aluminum powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the aluminum powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate;

[0005] The medium potential coating is formed by curing the medium potential coating, the medium potential coating comprises a medium potential base material and a curing agent, the medium potential base material is a mixture of polymethoxyphenylsiloxane, magnesium-aluminum alloy powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium-aluminum alloy powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate;

[0006] The low-potential coating is formed by curing the low-potential paint, which includes a low-potential base material and a curing agent. The base material is a mixture of polymethoxyphenylsiloxane, magnesium powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate.

[0007] Optionally, the mass ratio of the high potential base material to the curing agent is 100:10-15, the mass ratio of the medium potential base material to the curing agent is 100:12-18, and the mass ratio of the low potential base material to the curing agent is 100:15-20.

[0008] Optionally, the auxiliary agent accounts for 0.5% to 1% by weight of the mixture.

[0009] Optionally, the auxiliary agent is a dispersing auxiliary agent, a defoaming auxiliary agent and an anti-settling auxiliary agent.

[0010] Optionally, the curing agent is a mixture of vinyl polysilazane and a catalyst.

[0011] Optionally, the catalyst comprises 2% to 4% by weight of the curing agent mixture.

[0012] Optionally, the aluminum powder is aluminum powder prepared by nitrogen atomization, and has an average particle size of 3 μm to 10 μm.

[0013] Optionally, the magnesium-aluminum alloy powder is a flaky aluminum-based alloy powder in which magnesium accounts for 5% and an average flake diameter is 10 μm to 40 μm.

[0014] Optionally, the magnesium powder is flaky magnesium powder with an average flake diameter of 10 μm to 40 μm.

[0015] According to another aspect of an embodiment of the present invention, a method for preparing a potential gradient distribution type high-temperature anti-corrosion coating is also provided, which is used to prepare any of the above-mentioned coatings. The coating sequence is to sequentially coat a high potential coating, a medium potential coating and a low potential coating. The thickness of each layer is 30 μm to 40 μm, and the coating is cured at room temperature after coating.

[0016] The beneficial effect of the present invention is that a potential gradient distribution type high temperature anti-corrosion coating and a preparation method thereof are proposed, which greatly improves the protection efficiency of the cathodic protection coating through the superposition and adaptation of different potential layers, achieves a longer service life of the coating while effectively reducing the thickness, and extends the maintenance cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the structure of a potential gradient distribution type high temperature anti-corrosion coating according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] According to one aspect of an embodiment of the present invention, a potential gradient distribution type high temperature anti-corrosion coating is provided, such as Figure 1 As shown, the coating comprises three coatings, namely, a high potential coating, a medium potential coating and a low potential coating, which are sequentially stacked, wherein the high potential coating is formed by curing the high potential coating, and the high potential coating also comprises a high potential base material and a curing agent, wherein the high potential base material is a mixture of polymethoxyphenylsiloxane, aluminum powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the aluminum powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate;

[0020] The medium potential coating is formed by curing the medium potential coating, the medium potential coating comprises a medium potential base material and a curing agent, the medium potential base material is a mixture of polymethoxyphenylsiloxane, magnesium-aluminum alloy powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium-aluminum alloy powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate;

[0021] The low-potential coating is formed by curing the low-potential paint, which includes a low-potential base material and a curing agent. The base material is a mixture of polymethoxyphenylsiloxane, magnesium powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate.

[0022] Based on the high temperature stable film forming material polysilazane technology, the gradient potential matching coating is the core working principle of the present invention. The low potential coating is located on the surface of the coating structure. In a corrosive environment, since the coating is in contact with the steel substrate as a whole to form a closed loop, it can be seen from the principle of electrochemical corrosion that the low potential coating on the top layer has a priority self-sacrificial reaction compared to the medium and high potential coatings. Therefore, the medium and high potential coatings located in the lower layer do not undergo corrosion reactions, and the magnesium phase of the low potential coating gradually self-sacrifices. After a period of corrosion protection, the low potential coating on the top layer fails. At this time, the composition structure of the medium and high potential coatings has not changed. The medium potential coating begins to self-sacrificially react, and the failed low potential coating can play a role as a dielectric barrier due to the stacking of corrosion products. Based on the same principle, the appearance of corrosion products still does not affect the conductivity of the bottom cathode protection coating, and the passage of the corrosive medium is further delayed due to the stacking of a large number of corrosion products on the upper layer. The reaction does not begin to sacrificially react until the medium potential layer fails, and the high potential layer begins to undergo sacrificial reaction. The overall protection life of the coating can be much greater than that of traditional cathode protection coatings with a single potential distribution.

[0023] Furthermore, the mass ratio of the high potential base material to the curing agent is 100:10-15, the mass ratio of the medium potential base material to the curing agent is 100:12-18, and the mass ratio of the low potential base material to the curing agent is 100:15-20.

[0024] Furthermore, the auxiliary agent accounts for 0.5% to 1% of the weight of the mixture.

[0025] Furthermore, the auxiliary agent is a dispersing auxiliary agent, a defoaming auxiliary agent and an anti-settling auxiliary agent.

[0026] Furthermore, the curing agent is a mixture of vinyl polysilazane and a catalyst.

[0027] Furthermore, the catalyst accounts for 2% to 4% by weight of the mixture of the curing agent.

[0028] Furthermore, the aluminum powder is aluminum powder prepared by nitrogen atomization, and has an average particle size of 3 μm to 10 μm.

[0029] Furthermore, the magnesium-aluminum alloy powder is a flaky aluminum-based alloy powder in which magnesium accounts for 5% and an average flake diameter is 10 μm to 40 μm.

[0030] Furthermore, the magnesium powder is flaky magnesium powder with an average flake diameter of 10 μm to 40 μm.

[0031] According to another aspect of an embodiment of the present invention, a method for preparing a potential gradient distribution type high-temperature anti-corrosion coating is also provided, which is used to prepare any of the above-mentioned coatings. The coating sequence is to sequentially coat a high potential coating, a medium potential coating and a low potential coating. The thickness of each layer is 30 μm to 40 μm, and the coating is cured at room temperature after coating.

[0032] Example 1

[0033] 1. Preparation of high potential coating: weigh 250g of polymethoxyphenylsiloxane, 690g of high-purity aluminum powder with an average particle size of 10μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 50g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a high potential coating base material; weigh 96g of vinyl polysilazane and 4g of n-butyl titanate and mix them evenly to obtain a high potential coating curing agent.

[0034] 2. Preparation of medium potential coating: Weigh 330g of polymethoxyphenylsiloxane, 600g of flaky magnesium-aluminum alloy powder with an average flake diameter of 30μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 60g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a medium potential coating base; weigh 116g of vinyl polysilazane and 4g of n-butyl titanate and mix evenly to obtain a medium potential coating curing agent.

[0035] 3. Preparation of low-potential coating: weigh 350g of polymethoxyphenylsiloxane, 550g of flaky magnesium powder with an average flake diameter of 10μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 90g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a low-potential coating base; weigh 146g of vinyl polysilazane and 4g of n-butyl titanate and mix them evenly to obtain a low-potential coating curing agent.

[0036] 4. Coating: Mix high-potential paint and curing agent, apply to the surface of 45 steel substrate, the average coating thickness is 30μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 60μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 90μm, and then cure at room temperature for 5 days.

[0037] After testing, the steel parts protected by the coating showed no corrosion, blistering, cracking, peeling or powdering after 4200h cyclic aging test in CX corrosion environment, and the adhesion was as high as 15.3MPa. At the same time, it can withstand high temperature of 600℃ and baking for up to 1000h without cracking, and has excellent protective performance of 600℃ and neutral salt spray corrosion for 20 cycles.

[0038] Example 2

[0039] 1. Preparation of high potential coating: weigh 150g of polymethoxyphenylsiloxane, 730g of high-purity aluminum powder with an average particle size of 5μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 110g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a high potential coating base material; weigh 140g of vinyl polysilazane and 10g of n-butyl titanate and mix them evenly to obtain a high potential coating curing agent.

[0040] 2. Preparation of medium potential coating: Weigh 280g of polymethoxyphenylsiloxane, 650g of flaky magnesium-aluminum alloy powder with an average flake diameter of 40μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 60g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a medium potential coating base; weigh 210g of vinyl polysilazane and 10g of tetramethylguanidine and mix them evenly to obtain a medium potential coating curing agent.

[0041] 3. Preparation of low-potential coating: weigh 300g of polymethoxyphenylsiloxane, 600g of flaky magnesium powder with an average flake diameter of 40μm, 5g of dispersant BYK163, 5g of defoamer BYK052, and 90g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a low-potential coating base; weigh 256g of vinyl polysilazane and 14g of n-butyl titanate and mix them evenly to obtain a low-potential coating curing agent.

[0042] 4. Coating: Mix high-potential paint and curing agent, apply to the surface of 45 steel substrate, the average coating thickness is 40μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 80μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 120μm, and then cure at room temperature for 5 days.

[0043] After testing, the steel parts protected by the coating showed no corrosion, blistering, cracking, peeling or powdering after 5000h cyclic aging test in CX corrosion environment, and the adhesion was as high as 11.6MPa. At the same time, it can withstand high temperature of 600℃ and baking for up to 1000h without cracking, and has excellent protective performance of 600℃ and neutral salt spray corrosion for 20 cycles.

[0044] Example 3

[0045] 1. Preparation of high potential coating: weigh 200g of polymethoxyphenylsiloxane, 700g of high-purity aluminum powder with an average particle size of 3μm, 5g of dispersant BYK163, 2g of defoamer BYK054, and 95g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a high potential coating base; weigh 120g of vinyl polysilazane and 3g of tetramethylguanidine and mix them evenly to obtain a high potential coating curing agent.

[0046] 2. Preparation of medium potential coating: Weigh 300g of polymethoxyphenylsiloxane, 630g of flaky magnesium-aluminum alloy powder with an average flake diameter of 30μm, 4g of dispersant BYK110, 1g of defoamer BYK066N, and 65g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a medium potential coating base; weigh 230g of vinyl polysilazane and 12g of butyl titanate and mix evenly to obtain a medium potential coating curing agent.

[0047] 3. Preparation of low-potential coating: weigh 320g of polymethoxyphenylsiloxane, 580g of flaky magnesium powder with an average flake diameter of 10μm, 4g of dispersant BYK163, 1g of defoamer BYK052, and 95g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a low-potential coating base; weigh 244g of vinyl polysilazane and 16g of n-butyl titanate and mix them evenly to obtain a low-potential coating curing agent.

[0048] 4. Coating: Mix high-potential paint and curing agent, apply to the surface of 45 steel substrate, the average coating thickness is 40μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 70μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 100μm, and then cure at room temperature for 5 days.

[0049] After testing, the steel parts protected by the coating showed no corrosion, blistering, cracking, peeling or powdering after 4000h cyclic aging test in CX corrosion environment, and the adhesion was as high as 11MPa. At the same time, it can withstand high temperature of 600℃ and baking for up to 1000h without cracking, and has excellent protective performance of 600℃ and neutral salt spray corrosion for 20 cycles.

[0050] Example 4

[0051] 1. Preparation of high potential coating: weigh 210g of polymethoxyphenylsiloxane, 680g of high-purity aluminum powder with an average particle size of 10μm, 5g of dispersant BYK163, 2g of defoamer BYK052, and 103g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a high potential coating base; weigh 150g of vinyl polysilazane and 4g of tetramethylguanidine and mix them evenly to obtain a high potential coating curing agent.

[0052] 2. Preparation of medium potential coating: Weigh 310g of polymethoxyphenylsiloxane, 580g of flaky magnesium-aluminum alloy powder with an average flake diameter of 40μm, 8g of dispersant BYK110, 1g of defoamer BYK066N, and 61g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a medium potential coating base; weigh 220g of vinyl polysilazane and 10g of butyl titanate and mix them evenly to obtain a medium potential coating curing agent.

[0053] 3. Preparation of low-potential coating: weigh 340g of polymethoxyphenylsiloxane, 580g of flaky magnesium powder with an average flake diameter of 20μm, 4g of dispersant BYK110, 1g of defoamer BYK052, and 95g of butyl acetate, dehumidify, and grind to a fineness of 40μm to obtain a low-potential coating base; weigh 263g of vinyl polysilazane and 17g of n-butyl titanate and mix them evenly to obtain a low-potential coating curing agent.

[0054] 4. Coating: Mix high-potential paint and curing agent, apply to the surface of 45 steel substrate, the average coating thickness is 30μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 60μm, mix medium-potential paint and curing agent, continue to apply until the total coating thickness reaches 100μm, and then cure at room temperature for 5 days.

[0055] After testing, the steel parts protected by the coating showed no corrosion, blistering, cracking, peeling or powdering after 4200h cyclic aging test in CX corrosion environment, and the adhesion was as high as 12.9MPa. At the same time, it can withstand high temperature of 600℃ and baking for up to 1000h without cracking, and has excellent protective performance of 600℃ and neutral salt spray corrosion for 20 cycles.

[0056] The above is only a specific embodiment of the present invention, and the present invention is described in detail. The unexplained part is a conventional technology. However, the protection scope of the present invention is not limited to this. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A potential gradient distribution type high temperature anti-corrosion coating, characterized in that: The coating comprises three coatings, namely, a high potential coating, a medium potential coating and a low potential coating, which are sequentially stacked, wherein the high potential coating is formed by curing the high potential coating, and the high potential coating also comprises a high potential base material and a curing agent, wherein the high potential base material is a mixture of polymethoxyphenylsiloxane, aluminum powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the aluminum powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate; The medium potential coating is formed by curing the medium potential coating, the medium potential coating comprises a medium potential base material and a curing agent, the medium potential base material is a mixture of polymethoxyphenylsiloxane, magnesium-aluminum alloy powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium-aluminum alloy powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate; The low-potential coating is formed by curing the low-potential paint, which includes a low-potential base material and a curing agent. The base material is a mixture of polymethoxyphenylsiloxane, magnesium powder, an auxiliary agent and butyl acetate, wherein the polymethoxyphenylsiloxane accounts for 15% to 25% of the weight of the mixture, the magnesium powder accounts for 69% to 73% of the weight of the mixture, and the balance is butyl acetate.

2. The coating according to claim 1, characterized in that The mass ratio of the high potential base material and the curing agent is 100:10-15, the mass ratio of the medium potential base material and the curing agent is 100:12-18, and the mass ratio of the low potential base material and the curing agent is 100:15-20.

3. The coating according to claim 1, characterized in that The additive accounts for 0.5% to 1% of the weight of the mixture.

4. The coating according to claim 1, characterized in that The auxiliary agents are dispersing auxiliary agents, defoaming auxiliary agents and anti-settling auxiliary agents.

5. The coating according to claim 1, characterized in that The curing agent is a mixture of vinyl polysilazane and a catalyst.

6. The coating according to claim 5, characterized in that The catalyst accounts for 2% to 4% by weight of the curing agent mixture.

7. The coating according to claim 1, characterized in that The aluminum powder is prepared by nitrogen atomization, and has an average particle size of 3 μm to 10 μm.

8. The coating according to claim 1, characterized in that The magnesium-aluminum alloy powder is a flaky aluminum-based alloy powder with a magnesium content of 5% and an average flake diameter of 10 μm to 40 μm.

9. The coating according to claim 1, characterized in that The magnesium powder is flaky magnesium powder with an average flake diameter of 10 μm to 40 μm.

10. A method for preparing a potential gradient distribution type high temperature anti-corrosion coating, used for preparing any coating as claimed in claims 1 to 9, characterized in that: The coating sequence is to sequentially coat a high potential coating, a medium potential coating and a low potential coating, each layer having a thickness of 30 μm to 40 μm, and the coating is cured at room temperature.

Citation Information

Patent Citations

  • Magnesium-aluminum coated steel sheet and manufacturing method therefor

    CN105793463A

  • Anti-corrosion coating for cathode protection and preparation method of coating

    CN106563627A

  • System and method for cathodic protection by distributed sacrificial anodes

    CN109154089A

  • Protective coating of pipe wall, electroplating method and application

    CN112195489A

  • Marine environment resistant stealth material protection system based on interlayer potential difference control

    CN117229665A